Impact of tumor size, number of tumors and neutrophil‐to‐lymphocyte ratio in liver transplantation for recurrent hepatocellular carcinoma. Issue 7 (29th November 2012) - Yoshizumi, Tomoharu; Ikegami, Toru; Yoshiya, Shohei; Motomura, Takashi; Mano, Yohei; Muto, Jun; Ikeda, Tetsuo; Soejima, Yuji; Shirabe, Ken; Maehara, Yoshihiko
<x xml:space="preserve">Abstract</x> Aim Hepatocellular carcinoma (HCC) is primarily treated with hepatic resection and/or locoregional therapy. When HCC recurs and further treatment is no longer possible owing to poor liver function, liver transplantation (LT) or living‐donor LT (LDLT) is considered. The aim of this study was to clarify risk factors for tumor recurrence after LDLT in patients with recurrent HCC. Methods The study comprised 104 patients who had undergone LDLT because of end‐stage liver disease with recurrent HCC. The recurrence‐free survival rates after the LDLT were calculated. Risk factors for tumor recurrence were identified. Results The 1‐, 3‐ and 5‐year recurrence‐free survival rates were 89.6%, 80.3% and 78.4%, respectively. By univariate analysis, the factors affecting recurrence‐free survival were the sum of the largest tumor size and number of tumors of 8 or more (P < 0.0001), des‐γ‐carboxy prothrombin of more than 300 mAU/mL (P = 0.0001), and a neutrophil‐to‐lymphocyte ratio (NLR) of 4 or more (P = 0.0002), α‐fetoprotein of more than 400 ng/mL (P = 0.0001) and bilobar tumor distribution (P = 0.046). A multivariate analysis identified independent risk factors for post‐LDLT tumor recurrence including the sum of tumor size and number of tumors of 8 or more (P = 0.0004) and an NLR of 4 or more (P = 0.01). The 1‐ and 3‐ year recurrence‐free survival rates in the recipients who had both risk factors were 30.0% and 15.0%, respectively. Conclusion LDLT should not be performed for patients who have both independent risk factors after any treatments for HCC.